Duplex Evidence of Recanalization of Deep Venous Thrombosis with Conservative Management - Rahman, M; Azad, AK; Rahman, A; Aftabuddin, M (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2):234-6 The abstract of this article is available on the PubMed website